Arrest in ciliated cell expansion on the bronchial lining of adult rats caused by chronic exposure to industrial noise - Oliveira, MJR (2005)
Workers chronically exposed to high-intensity/low-frequency noise at textile plants show increased frequency of respiratory infections. This phenomenon prompted the herein investigation on the cytology of the bronchial epithelium of Wistar rats submitted to textile noise. Workplace noise from a cotton-mill room of a textile factory was recorded and reproduced in a sound-insulated animal room. The Wistar rats were submitted to a weekly schedule of noise treatment that was similar to that of the textile workers (8 h/day, 5 days/week). Scanning electron microscopy (SEM) was used to compare the fine morphology of the inner surface of the bronchi in noise-exposed and control rats. SEM quantitative cytology revealed that exposure to noise for 5-7 months caused inhibition in the natural expansion of the area occupied by ciliated cells on the bronchial epithelium as adult rats grow older. This difference between noise-exposed and age-matched control rats was statistically significant (P<0.05) and documents that the cytology of the rat bronchial epithelium is mildly altered by noise exposure. The decrease in the area of bronchial cilia may impair the mucociliar clearance of the respiratory airways and, thus, increase vulnerability to respiratory infection.